1968
DOI: 10.2466/pr0.1968.23.3.792
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of Morale in Resocialization of Pedophiles

Abstract: Successive sets of ratings given to a group of pedophiles revealed a downward trend in the ratings of their actual and their ideal selves. This seeming erosion in morale during 1 yr. suggests a potential for recidivism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In part, this finding led Frisbie et al to conclude that released offenders were "better integrated" than incarcerated offenders, but they noted that this could have been a reflection of their different situations, rather than personality differences. A 1-year follow-up of 79 of the released molesters (Dingman et al, 1968) showed that the respondents' views of both their real and ideal selves had declined. This was described in terms of erosion of morale and was related to concern about impending recidivism.…”
Section: The Cognition Literature On Child Molestationmentioning
confidence: 94%
See 1 more Smart Citation
“…In part, this finding led Frisbie et al to conclude that released offenders were "better integrated" than incarcerated offenders, but they noted that this could have been a reflection of their different situations, rather than personality differences. A 1-year follow-up of 79 of the released molesters (Dingman et al, 1968) showed that the respondents' views of both their real and ideal selves had declined. This was described in terms of erosion of morale and was related to concern about impending recidivism.…”
Section: The Cognition Literature On Child Molestationmentioning
confidence: 94%
“…One application of an expanded semantic differential with child molesters was provided by Frisbie and her colleagues (Dingman et al, 1968;Frisbie et al, 1967). They described the technique as "nonthreatening" and "relatively ambiguous" (Frisbie et al, 1967, p. 700), and they argued that it and similar psychological assessments are important "because an adult male's selection of a child as a sexual object seems to be related to his perceptions of the self, his role in a given social structure, and his recognhion and/or acceptance of ethical values and social expectations" (p. 699).…”
Section: The Cognition Literature On Child Molestationmentioning
confidence: 99%
“…The second approach to cognitive assessment involves a less focused examination of molesters' thoughts about themselves and others. Included here are such techniques as the semantic differential (Osgood, Suci, & Tannenbaum, 1957) that have been used with sexual offenders (Marks & Sartorius, 1967) including child molesters (Frisbie et aL, 1967;Dingman, Frisbie, & Vanasek, 1968;Quinsey, Bergersen, & Steinman, 1976). Although one's choice of the approach to assessment depends on a number of factors (e.g., specific research concerns, anticipated treatment outcomes), we have been more concerned with the second approach, in part to discover the general meanings of children and adults to child molesters, as well as their self-perceptions.…”
Section: Introductionmentioning
confidence: 99%